2021
DOI: 10.1002/adem.202100301
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution, Mechanical, and Corrosion Behavior of Cryogenic Friction Stir‐Processed AA2014 Alloy

Abstract: Herein, a large‐area stir zone (SZ) is fabricated in AA2014 alloy via overlapping friction stir processing (FSP). The microstructure and texture evolution of AA2014 alloy during FSP is examined using electron backscattered diffraction (EBSD). EBSD maps reveal recrystallized fine grains with high‐angle grain boundaries in SZ due to dynamic recovery (DRV) and continuous dynamic recrystallization (C‐DRX). Severe plastic straining induced by the tool leads to the formation of the A‐(110) <111> component. The textu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 42 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…The tool's intense plastic flow transforms the large aluminum grains into smaller ones, and the tool's movement helps the grains to distribute evenly. 6,2123 For a better understanding of the grain refinement across the bulk-area processing region, EBSD analysis was done at each overlapping pass OLFSP sample. The EBSD maps of the stir zone in each pass (labeled with A–E) of OLFSP samples are shown in Figures 3 and 4, and it has been noticed that the grain size of each pass is approximately the same in processing regions owing to the selection of optimum processing conditions (such as tool revolution rate and travel rate) and providing time gap between successive overlapping paths.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tool's intense plastic flow transforms the large aluminum grains into smaller ones, and the tool's movement helps the grains to distribute evenly. 6,2123 For a better understanding of the grain refinement across the bulk-area processing region, EBSD analysis was done at each overlapping pass OLFSP sample. The EBSD maps of the stir zone in each pass (labeled with A–E) of OLFSP samples are shown in Figures 3 and 4, and it has been noticed that the grain size of each pass is approximately the same in processing regions owing to the selection of optimum processing conditions (such as tool revolution rate and travel rate) and providing time gap between successive overlapping paths.…”
Section: Resultsmentioning
confidence: 99%
“…The deformed material is moved around the probe from the leading to the trailing edge (TA) and deposited beneath the shoulder. 2,3 FSP is a versatile technique for repairing casting defects, 4 local modifications of microstructure, 5 achieving grain refinement, 6 and producing surface composites in metals and alloys. 7 To accomplish these functions, singlepass FSP is carried out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corrosion potential (Ecor) extracted from the Tafel plots is also documented in table 2. Generally highest negative Ecor value indicates less corrosion resistance, whereas the lowest negative Ecor indicates high corrosion resistance [25][26][27]. The outcomes showed that CrMoV low alloy steels' corrosion resistance was improved by heat treatment followed by cryogenic treatment.…”
Section: Corrosionmentioning
confidence: 95%
“…Various overlapping percentages from 0 to 100 are taken into account when executing the OLFSP. As indicated by numerous publications, 3,10 overlapping with 50% was used in order to eradicate the advancing side and obtain additional grain refining. In the current investigation, a five-pass OLFSP was carried out by removing the advancing side.…”
Section: Selection Of Overlapping Ratiomentioning
confidence: 99%